Family characteristics as risk factors of stunting among children age 12-59 month - Khairani, Nurul; Effendi, Santoso Ujang (Universitas Aisyah Pringsewu, 2019)
Stunting in children (low height for age) increases morbidity and mortality rate. It can lead to poor intelligence and productivity, and degenerative diseases. The objective of this research was to investigate the associations of family characteristics with stunting in children aged 12-59 months who visited the integrated health posts in Ratu Samban District, Bengkulu City. The hypothesis of this research was there were associations of family characteristics with stunting in children aged 12-59 months who visited the integrated health posts in Ratu Samban District, Bengkulu City. This research was conducted in June, 2017. The type of the research was Analytical Survey and the design was Cross Sectional. The subject was mothers of children aged 12-59 months who visited the integrated health posts in Ratu Samban District, Bengkulu City. The sampling technique was Accidental Sampling and the sample number was 102 mothers. The data were collected by questionnaires and anthropometric assessment. Chi-Square test was used to assess the associations of family characteristics with stunting. The result showed that of 102 mothers, 32 mothers (31,37 percent) had stunted children. Family characteristics (maternal height (p=0.257), maternal education (p=0.455), paternal education (p=0.250), total of family member (p=0.245), and income of family head (p=0.320) were not associated with stunting and maternal knowledge (p=0.003) was associated with stunting. The researchers suggest to the community health center and the integrated health post can conduct nutrition education, and especially about stunting more intensively to increase the knowledge of productive woman, pregnant woman, and mother of children.